Consumers’ Propensity to Complain Towards Tourist Agencies’ Services: Evidence from Serbia and Croatia - Tomić, Slavica; Marić, Dražen; Leković, Ksenija; Jevtić, Jelena M (Industrija, 2018)
The goal of the research is to determine a statistically significant difference in the tendency to appeal in relation to socio-demographic characteristics of the users of tourist services. The study has been conducted on a group sample of 116 respondents from Serbia and 106 respondents from Croatia. The empirical part of the research was carried out by a survey technique. The results of the conducted empirical research confirmed the findings and claims of foreign authors on the impact of tourist service users’ age, monthly income and the number of family members, on their inclination to complain. The main findings of this research indicate that maintaining a long-term loyalty relationships with existing users is becoming increasingly difficult. The paper seeks to contribute to the existing literature by indicating the importance of knowing the effects of influence factors upon a tendency to file a complaint. The obtained results help employees in the first service line to identify aspects of influence on the users’ reaction to service failure and thus give a starting point for creating measures for effective resolution of user dissatisfaction. Future researchers are advised to collect additional information on the factors influencing the user’s complaint behaviour.